Are Family Firms Doing More Innovation Output With Less Innovation Input? A Replication and Extension. (July 2023) - Block, Joern; Hansen, Christopher; Steinmetz, Holger
The role of family firms in innovation and the question of whether family firms show differences in innovation investments and outcomes are intensely debated. To address these issues, Duran, Kammerlander, van Essen, and Zellweger (2016) published a meta-analytic structural equation model showing that family firms produce more innovation output with less innovation input. In the present article, we present the results of two empirical studies. Study 1 replicates the original methodological approach and study 2 provides an extension by using an updated and enlarged sample of 290 papers, adopting a more advanced multilevel approach, and controlling for firm age. The results show that while we could successfully replicate the original results of DKEZ in study 1, study 2 revealed only a weak negative effect of family firm status on innovation input and no effect on innovation output. Our results suggest that family firms are not producing more innovation output with less innovation input and that further research should focus on the heterogeneity within the group of family firms rather than simply comparing family to nonfamily firms. We close with a discussion of the methodological implications for meta-analyses in entrepreneurship research and a call for future research on family firm innovation. Our dataset and analytical procedures are publicly available.